2017
DOI: 10.1186/s12882-017-0549-y
|View full text |Cite
|
Sign up to set email alerts
|

Lower serum magnesium is associated with vascular calcification in peritoneal dialysis patients: a cross sectional study

Abstract: BackgroundCoronary artery calcification (CAC) is highly prevalent among dialysis patients and is associated with increased cardiovascular and all cause mortality. Magnesium (Mg) inhibits vascular calcification in animal and in-vitro studies but whether the same effect occurs in humans is uncertain.MethodsA single centre cross-sectional study of 80 prevalent peritoneal dialysis (PD) patients; on PD only for a minimum of 3 months. A radiologist blinded to patient status calculated their abdominal aortic calcific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 47 publications
3
37
0
Order By: Relevance
“…104 Serum magnesium concentration <0.8 mmol/L has been associated with a 36% increased risk of death from coronary artery disease 105,106 and 2 meta-analyses report serum magnesium is inversely associated with cardiovascular risk in both healthy controls and hemodialysis cohorts. 107,108 Similar findings were seen in a study of 80 patients on peritoneal dialysis, 109…”
Section: Improving Dialysis Adequacy and Renal Transplantationsupporting
confidence: 81%
See 1 more Smart Citation
“…104 Serum magnesium concentration <0.8 mmol/L has been associated with a 36% increased risk of death from coronary artery disease 105,106 and 2 meta-analyses report serum magnesium is inversely associated with cardiovascular risk in both healthy controls and hemodialysis cohorts. 107,108 Similar findings were seen in a study of 80 patients on peritoneal dialysis, 109…”
Section: Improving Dialysis Adequacy and Renal Transplantationsupporting
confidence: 81%
“…Serum magnesium concentration <0.8 mmol/L has been associated with a 36% increased risk of death from coronary artery disease and 2 meta‐analyses report serum magnesium is inversely associated with cardiovascular risk in both healthy controls and hemodialysis cohorts . Similar findings were seen in a study of 80 patients on peritoneal dialysis, with higher serum magnesium associated with less abdominal aortic calcification ( R 2 = .06, unstandardized coefficient [B] = −7.81, P = .03). Magnesium has also been reported to delay CPP maturation and transition from primary to secondary CPP in hemodialysis patients by slowing calcification propensity.…”
Section: Future Potential Management For Vc In Clinical Evaluationsupporting
confidence: 53%
“…We did not know the exact reasons why these factors were not positively correlated with AAC. Low serum magnesium level was also shown to be associated with vascular calcification in a cross-sectional study in PD patients, 19 and did not significantly affect AAC score in our study either. Coronary artery disease is highly prevalent in ESRD patients and results in a high mortality rate.…”
Section: Discussionsupporting
confidence: 45%
“…Limited information is currently available on the effects of Mg on arrhythmia, but Alabd et al reported that the post-dialysis QTc interval duration inversely correlated with a decrease in serum Mg levels during the HD session [61]. Table 1 shows observational studies that examined the relationship between serum Mg levels and cardiovascular calcification/atherosclerosis in CKD/ESRD patients [32,[62][63][64][65][66][67][68]. Most of these studies indicated an association between hypomagnesemia and cardiovascular lesions.…”
Section: Mg and Dialysis Therapymentioning
confidence: 99%